Student mobility and knowledge transfer in Malaysia: a case study of a renowned public university - Mohd Dzul Azzwan,; Ameera Ellyana Azhar, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Student mobility programmes offer an opportunity for students to study abroad while undertaking degree programmes in a local university. This paper took a closer look at the transfer of knowledge involved in these programmes by examining the reality experienced by the mobility students as revealed by the data collected after they completed their knowledge transfer programmes. Primary data were gathered via semi-structured qualitative interviews with 21 randomly sampled students of the Faculty of Economics and Management, National University of Malaysia who participated in the mobility programmes with various foreign universities across the world. The findings revealed that since there was language barrier, mobility students had the difficulty of communicating with other students especially in Korea and Japan as most of them were still unable to communicate in English. The mobility students also did not take a long time to adapt to the cultures of the foreign countries although they must still be alert because their social skills did not really improve their learning process. Nevertheless, the mobility students did benefit from the positive environment, excellent facilities, and refreshing learning patterns which were different from the UKM that had allowed them to learn comfortably apart from the usual opportunity of gaining new living experiences as well as new foreign friends.